Continuous hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-Methylphenol) in a fixed bed reactor - Garade, Ajit C.; Hengne, Amol M.; Deshpande, Tushar N.; Shaligram, Sayali V.; Shirai, Masayuki; Rode, Chandrashekhar V. (Journal of Chemical Engineering of Japan, 2009)
{Catalytic activity of various solid acid catalysts is evaluated for the continuous hydroxyalkylation of p-cresol to [

Cu:Al Nano catalyst for selective hydrogenolysis of glycerol to 1,2-propanediol - Mane, Rasika B.; Hengne, Amol M.; Ghalwadkar, Ajay A.; Vijayanand, Subramanian; Mohite, Pravin H.; Potdar, Hari S.; Rode, Chandrashekhar V. (Catalysis Letters, 2010)
Non-chromium Cu:Al nano catalyst prepared by simultaneous co-precipitation and digestion method without any template or stabilizer, showed three times higher activity than the bulk Cu-Cr catalyst for hydrogenolysis of glycerol in both isopropanol and water solvents, with the selectivity to 1,2-Propanediol (1,2-PDO) as high as 91% at 493 K and H(2) pressure of 7 MPa in 5 h. XRD pattern showed the presence of Cu(+) species in the activated Cu: Al nano catalyst. Although Cu(+) is catalytically inactive in glycerol hydrogenolysis reaction, the presence of Cu(+) helps to stabilize the particle size in a narrow range of 7-11 nm by inhibiting the sintering of copper particles under reaction conditions.
Keywords: 1; 2-Propanediol; Cu:Al nano catalyst; Glycerol; Selective hydrogenolysis

Selective hydrogenolysis of glycerol to 1,2-propanediol: comparison of batch and continuous process operations - Rode, Chandrashekhar V; Ghalwadkar, Ajay A.; Mane, R. B.; Hengne, Amol M.; Jadkar, Sachin T.; Biradar, Narayan S. (Organic Process Research & Development, 2010)
The screening of copper chromite catalysts with various promoters such as Al, Zn, and Ba for glycerol hydrogenolysis to 1,2-propanediol (1,2-PDO) in a batch reaction showed that Cu-Cr (Ba) catalyst gave the highest conversion of 34% and selectivity of 84% to 1,2-PDO. In a continuous operation (23 g catalyst bed) the same catalyst showed higher conversion of glycerol and selectivity for 1,2-PDO of 65% and > 90%, respectively, with an on-stream activity of similar to 800 h. Better performance in a continuous operation could be due to the in situ activation of the catalyst, suppression of glycerol cracking to ethylene glycol, as well as excessive hydrogenation of 1,2-PDO to 2-propanol due to lower contact time of 1.3 h as compared to that in a batch operation (5 h). Effects of various process parameters on conversion and selectivity also have been compared for batch and continuous operations.

Role of promoters in copper chromite catalysts for hydrogenolysis of glycerol - Mane, R. B.; Ghalwadkar, Ajay A.; Hengne, Amol M.; Suryawanshi, Y. R.; Rode, C. V. (Catalysis Today, 2011)
Various copper chromite catalysts with and without promoters were prepared by simultaneous co-precipitation and digestion technique and the role of promoters (Al, Ba and Zn) was investigated for hydrogenolysis of glycerol to 1,2-propylene glycol (1,2-PG) in both batch and continuous operations. Among various promoters studied, copper chromite catalyst with Ba as a promoter showed the highest activity and selectivity of 85% to 1,2-PG. This catalyst was found to be active for more than 800 h in a continuous operation also. Ammonia TPD results showed that barium promoted copper chromite catalyst had the highest acidity which facilitates the dehydration of glycerol to acetol which is the first step in hydrogenolysis of glycerol to 1,2-PG. The effect of barium content and variation in the promoters combination was also studied. (C) 2010 Elsevier B.V. All rights reserved.
1st Joint International Conference of the 8th Tokyo Conference on Advanced Catalytic Science and Technology/5th Asia Pacific Congress on Catalysis, Sapporo, JAPAN, JUL 18-23, 2010
Keywords: 1; 2-Propylene glycol; Acetol; Ammonia TPD; Glycerol hydrogenolysis; Surface acidity

Cu-ZrO2 nanocomposite catalyst for selective hydrogenation of levulinic acid and its ester to gamma-valerolactone - Hengne, Amol M.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Several copper based catalysts were prepared, characterized and evaluated for the hydrogenation of levulinic acid and its methyl ester. Among these, nanocomposites of Cu-ZrO2 and Cu-Al2O3 quantitatively catalyzed the hydrogenation of levulinic acid and its methyl ester to give 90-100% selectivity to gamma-valerolactone in methanol and water respectively. Both the Cu-ZrO2 and Cu-Al2O3 nanocomposites were prepared by the co-precipitation method using mixed precursors under controlled conditions. XRD results showed that the main active phase of the reduced Cu-ZrO2 catalyst was metallic copper and particle size was found to be of 10-14 nm by HRTEM. The active metal leaching was at a maximum for the Cu-Al2O3 catalyst in a water medium due to the formation of a copper-carboxylate complex that was blue in colour. Surprisingly, copper leaching was completely suppressed in the case of the Cu-ZrO2 catalyst in methanol in spite of the substrate loading was increased from 5 to 20% w/w. The excellent recyclability of the Cu-ZrO2 catalyst with complete LA conversion and > 90% GVL selectivity makes it a sustainable process having a commercial potential.

Surface species of supported ruthenium catalysts in selective hydrogenation of levulinic esters for bio-refinery application - Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Catalysis Letters, 2012)
Several supported noble metal catalysts were screened for the hydrogenation of methyl levulinate to gamma-valerolactone (GVL). Among these catalysts 5 % Ru/C showed the highest conversion of 95 % of methyl levulinate with 91 % selectivity to GVL. A detailed characterization was carried out using TPR, XRD, XPS and BET techniques. XPS studies revealed that higher extent of Ru-0 species in case of carbon supported Ru was responsible for its higher hydrogenation activity as compared to Ru on other supports. Effect of process parameters such as temperature, H-2 pressure, catalyst and substrate concentration and metal loading on methyl LA conversion and selectivity to GVL also has been studied. 5 % Ru/C catalyst was found to be stable up to five reuses.
Keywords: 5 % Ru/C; Biofeedstock; gamma-Valerolactone; H-2-TPR; Hydrogenation; Methyl levulinate; XPS

Single pot conversion of furfuryl alcohol to levulinic esters and gamma-valerolactone in the presence of sulfonic acid functionalized ILs and metal catalysts - Hengne, Amol M.; Kamble, Sumit B.; Rode, Chandrashekhar V. (Green Chemistry, 2013)
Ionic liquids functionalized with acidic anions, HSO4, ClSO3H, PTSA, TFA (MIm), HSO4 and TFA (NMP) were found to efficiently (99% conversion) catalyze the alcoholysis of furfuryl alcohol (FAL) in the presence of methanol, ethanol, n-butanol and isopropyl alcohol (IPA) to the corresponding levulinic acid esters under mild temperature (90-130 degrees C) conditions. The extended alkyl chain length of [MIm] using 1,4-butane sultone enhanced the Bronsted acidity of [BMIm-SH][HSO4] catalyst resulting into the highest selectivity of >95% to Me-LA. An increase in both temperature and catalyst concentration increased the furfuryl alcohol conversion and selectivity to levulinate esters. In contrast, an increase in the substrate concentration from 5 to 15% caused a decrease in Me-LA selectivity due to accumulation of intermediate ethers of furfuryl alcohol. Using a combination of [BMIm-SH][HSO4] and 5% Ru/C catalyst, direct conversion of FAL to gamma-valerolactone (GVL) is shown for the first time. A complete conversion of FAL with the highest selectivity of 68% to GVL could be achieved under optimum conditions while higher Ru loading enhanced the GVL selectivity to 94% in the hydrogenation step of this tandem approach. Our catalyst system could be efficiently recycled five times retaining the original activity and selectivity levels.

Single-pot formation of THFAL via catalytic hydrogenation of FFR over Pd/MFI catalyst - Biradar, Narayan S.; Hengne, Amol M.; Birajdar, Shobha N.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (ACS Sustainable Chemistry & Engineering, 2014)
Furfural (FFR) was selectively hydrogenated in a single pot to tetrahydrofurfuryl alcohol (THFAL) over a Si MFI molecular sieve supported Pd catalyst. Studies on catalyst screening revealed that both the metal function and the support were critical for directing the selectivity to the ringhydrogenated product, THFAL. The structural feature of MFI as shown by XRD was completely retained in the used sample of the 3% Pd/MFI catalyst confirming its stability under reaction conditions. XRD, along with SEM characterization of the used samples, established retention of morphology of the structured silicate, suggesting a strong interaction between hexagonal porous silicate and Pd particles. The complete conversion of FFR with an enhanced selectivity of 95% to THFAL could be achieved by recycling the crude of the first hydrogenation experiment over the same 3% Pd/MFI catalyst.
Keywords: Biomass conversion; Hydrogenation; Pd/MFI; Recyclability; THFAL

Surface synergism of an Ag-Ni/ZrO2 nanocomposite for the catalytic transfer hydrogenation of bio-derived platform molecules - Hengne, Amol M.; Malawadkar, Atul V.; Biradar, Narayan S.; Rode, Chandrashekhar V. (RSC Advances, 2014)
Levulinic acid was completely and selectively converted to GVL, in the presence of formic acid over an Ag-Ni/ZrO2 catalyst. The synergism between Ag and Ni in transfer hydrogenation eliminates the need for external hydrogen, making the process safer. The magnetic nature of the catalyst offers easy recovery for efficient recycling. This approach is standardized for the hydrogenation of several C-3-C-6 platform molecules in an aqueous medium.

Reductive cyclization of levulinic acid to gamma-valerolactone over non-noble bimetallic nanocomposite - Kadu, Brijesh S.; Hengne, Amol M.; Biradar, Narayan S.; Rode, Chandrashekhar V.; Chikate, Rajeev C. (Industrial & Engineering Chemistry Research, 2016)
Bimetallic nanoparticles have diverse applications in catalytic processes owing to the differences in individual properties that contribute to their increased catalytic activity. To further improve the efficiency, they are dispersed in an inert support that enhances the catalytic activity toward organic transformations. In this study, we report simple, facile, and cost-effective chemical route for the fabrication of nanocomposites with Fe-Ni bimetallic nanoparticles supported on montmorillonite (MMT) possessing variation in the Fe and Ni content. These composites are characterized with X-ray diffraction, transmission electron microscopy surface area, and NH3-TPD. Fe Ni bimetallic nanoparticles are well-dispersed within MMT structure having particle sizes of about 30-40 nm. Among various compositions of Fe-Ni/MMT catalysts, composite with 25% Fe and 25% Ni exhibits >99% LA conversion with 98% selectivity to GVL within 1 h. IPA is found to be better solvent for levulinic acid (LA) to gamma-valerolactone (GVL) conversion, while substantial leaching of iron takes place when water is used as a solvent. It is observed that bimetallic sites are responsible for reduction of LA, while strong acidic sites of MMT are favoring subsequent cyclization to GVL. XPS analysis of fresh and reused Fe-Ni/MMT composites suggest that the catalyst surface does not undergo any chemical change during successive cycles, and the catalytic activity is retained up to six cycles. The plausible mechanism for LA to GVL conversion involves reductive cyclization processes through formation of levulinate ester that undergoes lactonization due to synergism in bimetallic nanoparticles and MMT clay.

Single pot transfer hydrogenation and aldolization of furfural over metal oxide catalysts - Biradar, Narayan S.; Hengne, Amol M.; Sakate, S. S.; Swami, R. K.; Rode, Chandrashekhar V. (Catalysis Letters, 2016)
One pot catalytic transfer hydrogenation (CTH) of furfural to furfuryl alcohol (FAL) by using hydrogen producing alcohols and simultaneous aldolization of carbonyl compounds produced during CTH, with furfural was achieved over non-noble metal oxides with bifunctional sites. Basic sites of MgO responsible for abstraction of proton showed complete conversion of furfural to give FAL and C8 monomer in a ratio of 3:1, respectively, the later altered to 1:1 by incorporating Al into MgO. Catalyst stability was established by its four cycles study. [GRAPHICS]
Keywords: Aldol; furfural; Furfuryl alcohol; Metal oxides; transfer hydrogenation

Transfer hydrogenation of biomass-derived levulinic acid to gamma-valerolactone over supported Ni catalysts - Hengne, Amol M.; Kadu, Brijesh S.; Biradar, Narayan S.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (RSC Advances, 2016)
A sustainable process of catalytic transfer hydrogenation (CTH) of levulinic acid (LA) to gamma-valerolactone (GVL) was investigated over Ni on various supports (Al2O3, ZnO, MMT and SiO2) in the presence of isopropanol (IPA) as the H-donor. Among these, the montmorillonite (MMT) supported Ni catalyst showed almost complete LA conversion (>99%) and selectivity (>99%) to GVL within 1 h. XRD and XPS results showed that the concentration of the metallic species significantly enhanced (two to four times) in the recovered sample as compared to the freshly prepared Ni/MMT. This was due to the in situ reduction of Ni2+ species present on the catalyst surface, through liberated H-2 under the reaction conditions. The strong acid strength of MMT, evidenced by NH3-TPD and py-IR, facilitated the esterification of LA as well as cyclization to GVL. The conversion-selectivity pattern was found to decrease in the IPA-water mixture while, it remained unchanged in the IPA-acetone mixture. Our catalyst could be efficiently recycled up to five times with consistent CTH activity and selectivity to GVL. The plausible mechanism of LA to GVL conversion involves the formation of a levulinate ester with IPA that favours its simultaneous hydrogenation and cyclization in a spontaneous manner to give GVL and regenerating IPA for sustainability.

Single pot selective hydrogenation of furfural to 2-methylfuran over carbon supported iridium catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K-W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Green Chemistry, 2018)
Various iridium supported carbon catalysts were prepared and screened for the direct hydrogenation of furfural (FFR) to 2-methyl furan (2-MF). Amongst these, 5% Ir/C showed excellent results with complete FFR conversion and highest selectivity of 95% to 2-MF at a very low H-2 pressure of 100 psig. Metallic (Ir degrees) and oxide (IrO2) phases of Ir catalyzed the first step hydrogenation involving FFR to FAL and subsequent hydrogenation to 2-MF, respectively. This was confirmed by XPS analysis and some control experiments. At a low temperature of 140 degrees C, almost equal selectivities of FAL (42%) and 2-MF (43%) were observed, while the higher temperature (220 degrees C) favored selective hydrodeoxygenation. At optimized temperature, 2-MF was formed selectively while higher pressure and higher catalyst loading favored ring hydrogenation of furfural rather than side chain hydrogenation. With the combination of several control experimental results and detailed catalyst characterization, a plausible reaction pathway has been proposed for the selective formation of 2-MF. The selectivity to various other products in FFR hydrogenation can be manipulated by tailoring the reaction conditions over the same catalyst.

Preparation and activity of copper-gallium nanocomposite catalysts for carbon dioxide hydrogenation to methanol - Hengne, Amol M.; Yuan, Ding Jier; Date, Nandan S.; Saih, Youssef; Kamble, Sanjay P.; Rode, V. Chandrashekhar; Huang, Kuo-Wei (Industrial & Engineering Chemistry Research, 2019)
Copper (Cu) nanocomposite catalysts with gallium (Ga) and aluminum (Al) were prepared using the simultaneous coprecipitation digestion method. The catalysts were characterized by N-2 adsorption, N2O titration, XRD (X-ray diffraction), H-2-TPR (H-2 temperature-programmed reduction), XPS (X-ray photoelectron spectroscopy), and CO2-TPD (CO2 temperature-programmed desorption) techniques, and CO2 hydrogenation to methanol synthesis was performed. The use of Ga in Cu catalysts enhanced the weak basic sites more than the Cu catalysts with Al. With the CuGa nanocomposite formation, the catalyst showed a sequential reduction of CuO, for example, Cu+2 to Cu+ to Cu-0, and the Cu surface area was also high in comparison with CuAl. These findings confirmed that both the Cu surface area and CuO reducibility in the catalyst helped to boost the conversion of CO2, whereas selectivity to methanol was associated with the basicity of the catalyst. CuAl catalysts showed very poor selectivity to methanol despite CO formation, which could be due to the weak interaction of the CuAl nanocomposite catalysts compared to the CuGa nanocomposite catalysts.

One pot hydrogenation of furfural to 2-methyl tetrahydrofuran over supported mono- and Bi-metallic catalysts - Date, Nandan S.; Hengne, Amol M.; Huang, K. -W.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (ChemistrySelect, 2020)
2-Methyltetrahydrofuran is a valuable commercial product that can be obtained by direct hydrogenation of furfural. In the present study, among several carbon supported bimetallic Ir-Ni catalysts with different loadings screened, 4% Ir-4% Ni/C catalyst showed excellent activity in terms of direct conversion (99%) to 2-MeTHF with a maximum selectivity of similar to 74% at 220 degrees C and 750 psig, suppressing the formation of side chain as well as ring opening products. The catalytic activity was found to be mainly affected by catalyst preparation methods, metal loadings, surface composition, temperature, pressure and catalyst loading. HR-TEM and STEM revealed well dispersed Ir-Ni NPs having the particle sizes in the range of 2 to 5 nm. Different phases of Ir i. e. Ir degrees and IrO(2)as well as oxygen vacancies were found to be responsible for hydrogenation of furfural to 2-methyl furan while, Ni degrees and NiO were responsible for further hydrogenation to 2-MeTHF. The synergic effect between Ir and Ni was established through XPS, H-2-TPR analysis. With the help of some control experiments, the plausible reaction pathway was also proposed. The catalyst prepared by co-impregnation method found more effective than prepared by sequential addition method. At lower Ni loadings of 1% and 2%, low temperature of 160 degrees C as well as at low H(2)pressure of 250 psig, mixture of furfuryl alcohol and 2-methyl furan were formed selectively. Catalyst could be successfully reused up to 3 times without leaching of metals.
Keywords: 2-Methyltetrahydrofuran; Bimetallic catalyst; furfural; Hydrogenation; OER type mechanism